Analisis Peranan Masyrakat Serta Perlindungan Hukum Terhadap Kids Influencer Sebagai Bentuk Lain dari Eksploitasi Anak - Kayus Kayowuan Lewoleba; Khairunisa Syalsabila (IAI Nasional Laa Roiba Bogor, 2024)
In the rapidly evolving digital era like today, the phenomenon of kidfluencers or kids influencers has emerged as an intriguing aspect, sparking debates regarding another form of exploitation of children. Kid influencers are children who become influencers on social media by sharing content about their daily lives, often utilized to promote certain products or brands as well. While some argue that this phenomenon can serve as a platform for expressing children's talents and creativity, many also express concerns about the potential exploitation that may occur. This journal elaborates on the role of society towards kid influencers as another form of child exploitation. Society plays a dual role in this phenomenon, where they can act as watchdogs to prevent exploitation or, conversely, exploit the popularity of these children for personal gain. In the legal context, there is a need for stronger protection for children who become influencers. However, Indonesia itself has not yet established specific regulations regarding kid influencers, although some laws and government regulations can serve as a basis for protecting children from exploitation. Protecting children who become kid influencers requires a comprehensive approach, involving the role of the government, parents, and society as a whole. This includes creating clear regulations, enhancing education, developing guidelines, and implementing an effective reporting system to prevent child exploitation. Awareness of the dangers of child exploitation also needs to be raised, as well as the importance of reporting content that is suspected of exploiting children to the authorities. Thus, legal protection and societal awareness are crucial steps in safeguarding the well-being of children in this complex phenomenon of kid influencers.